2022
DOI: 10.1001/jamanetworkopen.2021.44776
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Psychological Distress Among US Adults During Different Phases of the COVID-19 Pandemic

Abstract: This survey study assesses trends in psychological distress among US adults surveyed during 4 different phases of the COVID-19 pandemic in 2020 and 2021.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 5 publications
2
17
1
Order By: Relevance
“…While some studies have examined this in the context of “western” cultures where older adults are more isolated and may live in retirement facilities, the context in China is different, with most older adults living with their spouses. Nevertheless, consistent with findings in other countries (Lorant et al, 2021; McGinty et al, 2022; Sams et al, 2021; Xiong et al, 2020), results show elevated distress, particularly when compared to the general population or medical outpatients more broadly (e.g., 5-10% depressive symptoms) (Bradley and Rumsfeld, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…While some studies have examined this in the context of “western” cultures where older adults are more isolated and may live in retirement facilities, the context in China is different, with most older adults living with their spouses. Nevertheless, consistent with findings in other countries (Lorant et al, 2021; McGinty et al, 2022; Sams et al, 2021; Xiong et al, 2020), results show elevated distress, particularly when compared to the general population or medical outpatients more broadly (e.g., 5-10% depressive symptoms) (Bradley and Rumsfeld, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…In addition to the pandemic, 2020 saw the public murder of George Floyd by police ( Curtis et al., 2021 ), international demonstrations regarding anti-Black violence, elevated anti-Asian discrimination and violence ( Wu et al., 2021 )– ( Kormendi and Brown, 2021 ), and a divisive presidential election ( Blanchflower and Bryson, 2021 ). Overall, 2020 was marked by increases in stressors, depressive symptoms, psychological distress, and mental health problems ( McGinty et al., 2022 )– ( Ettman et al., 2022 ), which are critically important for shaping population health ( Becker and Kleinman, 2013 ), ( Moreno et al., 2020 ). However, the changes to mental health in 2020 also coincided with broader societal shifts in the past decade that have likely dramatically restructured the mental health of the American population; increasing dissemination of videos of police brutality ( Bor et al., 2018 ), amplified consumption of social media ( Keles et al., 2020 ), the legacy of the Great Recession/increased economic vulnerability ( Case and Deaton, 2015 ), a polarizing presidential administration ( Morey et al., 2021 ), and increasing frequency/severity of climate events ( Ebi et al., 2021 ), ( Cianconi et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the general U.S. adult population during the spring of 2020, clinically significant levels of anxiety and depression were reported, particularly among young adults [ 37 39 ]. Persistently elevated psychological distress among U.S. adults spanning from April 2020 through August 2021 in comparison to consistent prevalence rates of 3–4% prior to the onset of the COVID-19 pandemic demonstrate the ongoing impact on mental health [ 40 ]. Although several studies have reported a decline or cessation of e-cigarette use among many populations during the pandemic because of factors such as lack of accessibility due to stay-at-home orders and smoke shop closures, some proportion of young adults increased their use of e-cigarettes [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%